LANSKAP EKOLOGI KESERASIAN DAN KEMENARIKAN KEPARIWISATAAN ALAM DI WILAYAH YOGYAKARA UTARA - Muhamad muhamad (Universitas Gadjah Mada, 2014)
This study examines the extent of landscape ecology and attractiveness of the natural environment in the tourism area in the region north of Yogyakarta. Yogyakarta northern region has objects and natural tourism attractions of the venture capital in its tourism development footprint. The compatibility and attractiveness level of the environment is one of the most important factors to determine the region’s level of potential environmental compatibility and attractiveness, so that the characteristics and the distribution pattern of the attractiveness and harmony of nature in the tourism region can be known. The results showed that the landscape level of ecological harmony and the attractiveness of the environment after the 2010 eruption had a significant amount of the index. The higher the quality of the natural (physical) environment and social (human and socioeconomic) culture is, the higher the level of harmony and attractiveness of the region. Landscape ecology establishes harmony between the social component (population) and the natural environment (bio-physical), suchthat they form a potential tourist attraction at the site of nature tourism in the region north of Yogyakarta.